2015
DOI: 10.1002/adma.201502489
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Nanoelectrode Arrays to Monitor the Dopaminergic Differentiation of Human Neural Stem Cells

Abstract: A novel cell-based biosensing platform (Large-scale Homogeneous Nanoelectrode Arryas, LHONA) is developed using a combination of sequential laser interference lithography and electrochemical deposition methods. This enables the sensitive discrimination of dopaminergic cells from other types of neural cells in a completely non-destructive manner owing to its enhanced biocompatibility and excellent electrochemical properties. As such, this platform/detection strategy holds great potential as an effective non-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 36 publications
(19 reference statements)
0
68
0
Order By: Relevance
“…Various methods designed for sensing applications, such as nanostructured materials, [4][5][6] metafilms, [7] carbon dots, [8,9] electrodes [10,11] and elastic nanocomposite cilia structures, [12] and wearable sensors have been reported. The monitoring of the nanoparticles in air is necessary for safety control, because nanoscale particles generated from vehicles and industrial processes can penetrate the lungs and spread to other organs, resulting in serious respiratory and cardiac diseases.…”
Section: Doi: 101002/adma201604920mentioning
confidence: 99%
“…Various methods designed for sensing applications, such as nanostructured materials, [4][5][6] metafilms, [7] carbon dots, [8,9] electrodes [10,11] and elastic nanocomposite cilia structures, [12] and wearable sensors have been reported. The monitoring of the nanoparticles in air is necessary for safety control, because nanoscale particles generated from vehicles and industrial processes can penetrate the lungs and spread to other organs, resulting in serious respiratory and cardiac diseases.…”
Section: Doi: 101002/adma201604920mentioning
confidence: 99%
“…We previously reported the electrical impedance characterization of human mesenchymal stem cell (hMSC) growth [29], hMSC differentiation into adipocytes [30], osteogenic differentiation of hMSCs [31], neural differentiation of hMSCs [32], adipose tissue-derived stem cell (ADSC) growth [33], and senescence of ADSCs [34]. Additionally, the effect of the electrode material and structure patterned by nanoparticles [35], graphene [36], or a mixture of nanoparticles and graphene [37] on stem cell differentiation was investigated. Our experiments in which we measured the electrochemical signals of differentiated or undifferentiated stem cells showed that the electrochemical signature can be used to quantify the pluripotency of the stem cells [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this importance of dopamine, it has been reported that insufficient dopamine levels in the blood, or the loss of dopaminergic neurons in the brain, could result in a number of severe neurological diseases such as Parkinson's disease, drug addiction, psychosis, and attention deficit hyperactivity disorder (ADHD) [6,7]. To address this issue, numerous studies have reported various methods for the detection of dopamine in a highly sensitive and selective manner, which could be readily utilized for the early diagnosis of dopamine-related neurological diseases [8][9][10]. 2 of 11 Among the currently available methods (e.g., ELISA, colorimetric methods, Raman, HPLC) [11][12][13], the electrochemical-detection technique is considered one of the most efficacious tools for dopamine detection, owing to its convenience, rapid detection time, and cost effectiveness [14].…”
Section: Introductionmentioning
confidence: 99%